Introduction au dossier « Inscriptions urbaines américaines : rapports d’autorités » - Jean-Baptiste Barra; Timothée Engasser; Modesta Suárez (Les Cahiers de Framespa)
This issue is dedicated to the contemporary American urban space through the experience of inscriptions on walls and their social connections. This also highlights : some conflicts between several actors (writers, inhabitants, institutions) but also different initiatives of negotiations. Whether they are graffitis, tags, pixação or mural, these writings reveal several lines of tension, even conflict. However the studies united here, both multidisciplinary and transmediatic, allow us to point out fractures in perpetual evolution and oscillation between violence and recognition ; reflections that erase national o local frontiers ; orientations and answers thathelp us to model part of the urban popular culture (including music and cinema) on the entire American continent.